2006
DOI: 10.1038/sj.onc.1209672
|View full text |Cite
|
Sign up to set email alerts
|

Identification of secondary structure in the 5′-untranslated region of the human adrenomedullin mRNA with implications for the regulation of mRNA translation

Abstract: Adrenomedullin (AM) is a multifunctional regulatory peptide with important angiogenic and mitogenic properties. Here we identify a region of stable secondary structure in the 5 0 -untranslated region (5 0 UTR) of human AM mRNA. Reverse transcriptase-polymerase chain reaction of the 5 0 UTR consistently resulted, in addition to the product with the expected size of 155 base pair (bp), in a second product with an B65-bp deletion from the central region of the 5 0 UTR, suggesting the presence of a secondary struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Stable secondary RNA structures in the 5′-UTRs of mRNAs have been shown to regulate translation , . In fact, RNA G-quadruplexes containing short or one-nucleotide loops have been found to be extremely stable and can inhibit translation ,, .…”
Section: Discussionmentioning
confidence: 99%
“…Stable secondary RNA structures in the 5′-UTRs of mRNAs have been shown to regulate translation , . In fact, RNA G-quadruplexes containing short or one-nucleotide loops have been found to be extremely stable and can inhibit translation ,, .…”
Section: Discussionmentioning
confidence: 99%
“…26,[28][29][30][31][32][33] A stem-loop structure in exon 1 of the human ADM gene has been reported that participates in the regulation of ADM transcription. 34 In mice, the ADM gene is located in chromosome 7. It has an amino acid similarity of 60% with the human ADM gene.…”
Section: Gene Structurementioning
confidence: 99%
“…Commonly, the secondary structures of the 5Ј UTR have been characterized as down-regulators of gene expression. They are capable of inhibiting gene transcription process (Curie and McCormick 1997), accelerating mRNA degradation rate (Muhlrad et al 1995;Stefanovic et al 2000;Cannons and Cannon 2002), or reducing translation eYciency (Kozak 1989;Vega Laso et al 1993;Muhlrad et al 1995;Hess and Duncan 1996;Wood et al 1996;McCarthy 1998;Hua et al 2001;Myers et al 2004;Brenet et al 2006;Bunimov et al 2007).…”
Section: Introductionmentioning
confidence: 99%